Implementasi Kebijakan Sistem Informasi Manajamen Pertanahan Nasional Di Kantor Pertanahan Kota Manado - Ruruk, Meryansi Sappe; LALOMA, ALDEN; Pombengi, Jericho DANGA (Sam Ratulangi University, 2016)
ABSTRACT : Information System Management of the National Land policy issued by the government tohelp communities in the rapid completion of the maintenance of land given the land is something lastingand useful for humans. Implementation of the policy of the National Land Management InformationSystem is still not going well, so this research to answer the question of how the policy implementation ofthe National Land Management Information System. In this study, the researchers limited the ModelPolicy of Edward III, communications, resources and attitude.and researchers also see from the qualityfactor of services that exist in the land office Manado. This study uses descriptive qualitatively approachthrough in-depth interviews to 10 informants, observation and search for additional documents in theform of a list of guidelines for the interview, a tape recorder and stationery. The results showed that theoverall implementation of the national land management information system has not done well.Keywords: Policy Land Management Information System (SIMTANAS) Communication, Resources,attitude and quality of service.